Macromolecular Viral Entry Inhibitors as Broad‐Spectrum First‐Line Antivirals with Activity against SARS‐CoV‐2. Issue 20 (11th May 2022) - Groß, Rüdiger; Dias Loiola, Lívia Mesquita; Issmail, Leila; Uhlig, Nadja; Eberlein, Valentina; Conzelmann, Carina; Olari, Lia‐Raluca; Rauch, Lena; Lawrenz, Jan; Weil, Tatjana; Müller, Janis A.; Cardoso, Mateus Borba; et al.
Abstract: Inhibitors of viral cell entry based on poly(styrene sulfonate) and its core–shell nanoformulations based on gold nanoparticles are investigated against a panel of viruses, including clinical isolates of SARS‐CoV‐2. Macromolecular inhibitors are shown to exhibit the highly sought‐after broad‐spectrum antiviral activity, which covers most analyzed enveloped viruses and all of the variants of concern for SARS‐CoV‐2 tested. The inhibitory activity is quantified in vitro in appropriate cell culture models and for respiratory viral pathogens (respiratory syncytial virus and SARS‐CoV‐2) in mice. Results of this study comprise a significant step along the translational path of macromolecular inhibitors of virus cell entry, specifically against enveloped respiratory viruses. Abstract : Macromolecules are shown herein to act as broadly acting antiviral agents, most importantly against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), by interacting with the viruses thereby inhibiting viral entry. Antiviral activity is demonstrated in vitro against a panel of viruses, and in vivo against two respiratory pathogens (respiratory syncytial virus (RSV) and SARS‐CoV‐2). With due optimization, polymers hold translational promise as first‐line broad‐spectrum antivirals.